REPRESENTASI LATAR BELAKANG KONFLIK NAZI DAN YAHUDI PADA SERIAL ANIME ATTACK ON TITAN - Tampubolon, Yohannes; ABIDIN, SHOLIHUL (LPPM Universitas Putera Batam, 2023)
The similarities between Attack on Titan and the history of human civilization can be seen during World War II, when the Nazis rose to power in Germany in 1933, which was the first year the Nazis established concentration camps (Ghetto) to separate and imprison Jews, political opponents, and people who were considered inferior such as homosexuals, Roma people (Gypsies), some Slavic peoples (Russians, Poles and others) and people with disabilities. The purpose of this study is to determine the results of the representation of the background of the Nazi and Jewish conflict in the attack on titan anime series. The research method used is descriptive research conducted using a qualitative approach and using the semiotic analysis method. The researcher will observe in depth the Scene pieces from the anime series entitled attack of titan with a total of 10 scenes, the data collection used is documentation and literature study, the analysis flow follows the interactive analysis model as expressed by Miles and Huberman, namely data collection, data reduction, data presentation and conclusion drawing. The results show the anime